2012
DOI: 10.1073/pnas.1205147109
|View full text |Cite
|
Sign up to set email alerts
|

Microbial shifts in the swine distal gut in response to the treatment with antimicrobial growth promoter, tylosin

Abstract: Antimicrobials have been used extensively as growth promoters (AGPs) in agricultural animal production. However, the specific mechanism of action for AGPs has not yet been determined. The work presented here was to determine and characterize the microbiome of pigs receiving one AGP, tylosin, compared with untreated pigs. We hypothesized that AGPs exerted their growth promoting effect by altering gut microbial population composition. We determined the fecal microbiome of pigs receiving tylosin compared with unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
172
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(224 citation statements)
references
References 35 publications
43
172
2
7
Order By: Relevance
“…Studies of changes in microbial communities with in-feed antibiotics have detected shifts in bacterial membership and functions in swine feces (Allen et al, 2011;Kim et al, 2012;Looft et al, 2012), but have not addressed localized communities in the gut. Feces often serve as a proxy for the gut microbiota because they can be harvested readily and frequently, but fecal bacteria are a composite of potentially discrete upstream populations (Suchodolski et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of changes in microbial communities with in-feed antibiotics have detected shifts in bacterial membership and functions in swine feces (Allen et al, 2011;Kim et al, 2012;Looft et al, 2012), but have not addressed localized communities in the gut. Feces often serve as a proxy for the gut microbiota because they can be harvested readily and frequently, but fecal bacteria are a composite of potentially discrete upstream populations (Suchodolski et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports showed that sulfonamides and chloramphenicol could easily reach ground water, while fluoroquinolones could not leach. The reports added that in most areas of intensive livestock breeding, the source of contamination mainly attributed to irrigation with sewage [12,16]. The uptake and accumulation of antibiotics into edible plants is commonly initiated when expose to contaminated soil with considerable concentrations of the drugs over time as confirmed by several studies [59][60][61][62][63].…”
Section: Risk and Impact Of Veterinary Antibiotics On Human Health Anmentioning
confidence: 94%
“…The uptake and accumulation of antibiotics into edible plants is commonly initiated when expose to contaminated soil with considerable concentrations of the drugs over time as confirmed by several studies [59][60][61][62][63]. However significant amounts of antibiotics and/or their degraded metabolites are introduced to agro-system via irrigation, fertilization with antibiotic-polluted manures, bio-solids, sludge, sediments and contaminated water [16,64]. Accumulation and transport of antibiotics to edible plants poses high risk to crops, soil and water ecosystems [63,65,66], consequently, increasing risk to both human health and environment [3].…”
Section: Risk and Impact Of Veterinary Antibiotics On Human Health Anmentioning
confidence: 95%
See 2 more Smart Citations